Suppression of amino acid and oligopeptide mineralization by organic manure addition in a semiarid environment - Iqbal, S.; Jones, D.L.; Arif, M.S.; Yasmeen, T.; Xu, J.C.; Khan, S.; Nadir, S. (Wiley, 2020)
The rapid mineralization of organic nitrogen (ON) in semiarid soils frequently results in large N losses, reduced crop yields, and environmental pollution. The addition of manures to soil has the potential to promote microbial growth, increase N immobilization, reverse the decline in soil organic matter, and enhance soil quality. In this study, three contrasting organic manures were used to determine their influences on amino acid and oligopeptide dynamics in soil (as key component of the soil ON‐cycle) as well their effects on the size of the microbial biomass and N immobilization. Laboratory incubation experiments were set up with soil obtained from experimental field trial sites for growing maize. Treatments included soil amended with either poultry manure (PM), farmyard manure, pressmud, or unamended (control). Radio‐ and stable‐isotope (14C–15N) techniques were used to assess ON mineralization, immobilization, and leaching using the amino acids alanine and valine as well as the oligopeptides trialanine and valine–proline–proline as model substrates. Quantitative polymerase chain reaction was used to determine soil bacterial biomass. The results showed that all manures increased microbial growth and total soil amino acids as well as protein content. Greater immobilization and subsequently lower mineralization and leaching were also observed in the manure‐amended soils, with this being most pronounced in the PM treatment. The application of PM also enhanced the half‐lives of the ON compounds in soil and increased the size of the bacterial biomass. Overall, our findings indicate that manure amendments, particularly PM, can help promote more efficient ON cycling in semi‐arid ecosystem by controlling N mineralization, reducing amino acid leaching, and elevating oligopeptide immobilization.